2016
DOI: 10.1523/jneurosci.0774-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Tau-Driven Neuronal and Neurotrophic Dysfunction in a Mouse Model of Early Tauopathy

Abstract: Tauopathies are neurodegenerative diseases characterized by intraneuronal inclusions of hyperphosphorylated tau protein and abnormal expression of brain-derived neurotrophic factor (BDNF), a key modulator of neuronal survival and function. The severity of both these pathological hallmarks correlate with the degree of cognitive impairment in patients. However, how tau pathology specifically modifies BDNF signaling and affects neuronal function during early prodromal stages of tauopathy remains unclear. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 92 publications
8
50
0
Order By: Relevance
“…Inspection of the retina has been suggested as a potential biomarker for the diagnosis of neurodegeneration [24–26]. There is a higher incidence of age-related macular degeneration in patients with AD [27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inspection of the retina has been suggested as a potential biomarker for the diagnosis of neurodegeneration [24–26]. There is a higher incidence of age-related macular degeneration in patients with AD [27].…”
Section: Introductionmentioning
confidence: 99%
“…Tau oligomers were recently found in the retina of a rat model for glaucoma and suppression of tau reduced the occurrence of retinal degeneration [28]. Also, there is evidence of large protein deposits, such as Aβ and tau, being present in the retina of AD patients and in tauopathy mice as well as the presence of inflammation [24–26, 29, 30]. Early detection of AD, possibly even prodromal detection, would allow for the early intervention and prevention of neurodegeneration prior to major synapse loss and cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that BDNF expression levels can decrease in models of POD and AD, with IL-1β [40,135,166,136], Aβ [226229], and tau [230] directly affecting BDNF-associated intracellular signaling pathways and synaptic plasticity. Clinical studies in patients with the BDNF Val66Met polymorphism find that cognitive impairments associated with changes in BDNF occur more in preclinical stages of AD and not in advanced stages of AD (defined by high Aβ deposits) [231233].…”
Section: Discussionmentioning
confidence: 99%
“…Further, recombinant Tau fibrils induce aggregation of intracellular full‐length Tau in cultured cells (Kfoury et al, ). In vivo, injection of brain extracts from the P301S Tau transgenic model of tauopathy or from human AD brain into the brains of mice expressing wild type human Tau induces assembly of wild type Tau into filaments and spreading of Tau pathology across the brain (Clavaguera et al, ; Mazzaro et al, ). Similar results were obtained with injection of filaments of recombinant human Tau, which cause rapid induction of Tau inclusions in the site of injection and subsequent propagation of Tau pathology to interconnected areas (Iba et al, ).…”
Section: Introductionmentioning
confidence: 99%